Cuproptosis-related genes and agents: implications in tumor drug resistance and future perspectives - Xu, Lingwen; Cao, Xiaolan; Deng, Yuxiao; Zhang, Bin; Li, Xinzhi; Liu, Wentao; Ren, Wenjie; Tang, Xuan; Kong, Xiangyu; Zhang, Daizhou (Frontiers in Pharmacology, 2025)
In the field of tumor treatment, drug resistance remains a significant challenge requiring urgent intervention. Recent developments in cell death research have highlighted cuproptosis, a mechanism of cell death induced by copper, as a promising avenue for understanding tumor biology and addressing drug resistance. Cuproptosis is initiated by the dysregulation of copper homeostasis, which in turn triggers mitochondrial metabolic disruptions and induces proteotoxic stress. This process specifically entails the accumulation of lipoylated proteins and the depletion of iron-sulfur cluster proteins within the context of the tricarboxylic acid cycle. Simultaneously, it is accompanied by the activation of distinct signaling pathways that collectively lead to cell death. Emerging evidence highlights the critical role of cuproptosis in addressing tumor drug resistance. However, the core molecular mechanisms of cuproptosis, regulation of the tumor microenvironment, and clinical translation pathways still require further exploration. This review examines the intersection of cuproptosis and tumor drug resistance, detailing the essential roles of cuproptosis-related genes and exploring the therapeutic potential of copper ionophores, chelators, and nanodelivery systems. These mechanisms offer promise for overcoming resistance and advancing tumor precision medicine. By elucidating the molecular mechanisms underlying cuproptosis, this study aims to identify novel therapeutic strategies and targets, thereby paving the way for the development of innovative anti-cancer drugs.